The framing of the emigration discourse in Lithuanian online dailies - Nabažaitė, Erika (Information & Media, 2017)
Primarily, mass media, together with online dailies, which became popular due to its activity changes, makes an increasing impact on thinking, beliefs and conduct of the society. By emphasizing aspects of various actual social issues of the society in news agendas, such as emigration, and framing them in a discourse, mass media influences an attitude of the society toward the issue of emigration; it forms an assessment of the country of origin and induces to make decisions whether to stay or leave a country. The article presents the results of a pilot research of emigration discourse framing in Lithuanian online dailies delfi.lt and 15min.lt. Precisely, the research aims at examining an emigration discourse constructed in Lithuanian online dailies and identifying the role of mass media in representing an issue of emigration. The research is carried out by combining the methods of a quantitative content analysis and a critical discourse analysis under the discourse research methodology of N. Fairclough.Furthermore, the research has revealed that the role of mass media in representing emigration can be assessed as a formation of tendencies and regularities that motivate to depart from Lithuania. The pursuit of mass media to form tendencies is revealed by a demand to enlighten an issue of emigration in a field of political realities and international events, which are particularly significant to Lithuania, to provide a topic of emigration in the most readable news sections of online dailies, not describing it in detail, but relating it to the most favorable public realities, namely, the welfare of the people and the financial situation of the country. The issue of emigration presented in mass media is constructed by a negative one-sided discourse, which forms positive frames of emigration. Moreover, it has been ascertained that a negative valuation of Lithuania as the country of origin is predominant in online dailies. There are very distinct tendencies to propagate an economic migration, whereas a positive evaluation of the country is very abstract and it does not reveal any specific peculiarities of Lithuania, which would be a reason to stay in this country. Finally, the emigration discourse in online dailies can by characterized by an emotional, biased rhetoric, which further intensifies an expression of tendencies formed by mass media.
Keywords: ...